2013
DOI: 10.3109/02656736.2012.753738
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of bevacizumab and hyperthermia in a rodent model of hyperthermic intraperitoneal chemotherapy (HIPEC)

Abstract: The results of this study suggest that bevacizumab is not promising for clinical implementation in the setting of HIPEC: the effects on tumour size were ambivalent and there was no statistically significant benefit in TGD. The effects of hyperthermic perfusion in this study were negative: a higher blood concentration of oxaliplatin as compared to normothermic perfusion, without a higher intra-tumoural concentration. There was a higher mortality rate after hyperthermic perfusion as compared to normothermic perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Even preclinical trials report a significant increase in morbidity in mice when hyperthermia and bevacizumab are combined (109). At present, it is difficult to deprive a patient from a treatment based on Level I evidence suggesting an alternative therapeutic strategy that is not universally accepted because of the lack of irrefutable evidence.…”
Section: Topic 6: What Is the Best Timing As Far As Results Are Concementioning
confidence: 99%
See 1 more Smart Citation
“…Even preclinical trials report a significant increase in morbidity in mice when hyperthermia and bevacizumab are combined (109). At present, it is difficult to deprive a patient from a treatment based on Level I evidence suggesting an alternative therapeutic strategy that is not universally accepted because of the lack of irrefutable evidence.…”
Section: Topic 6: What Is the Best Timing As Far As Results Are Concementioning
confidence: 99%
“…Moreover, studies on colon cancer report a 3 to 4 times greater risk of perforations and fistulae in patients who received HIPEC in combination with bevacizumab and a doubled mortality rate even when the time interval between the administration of bevacizumab and the surgical procedure follows the safety indications (6-7 weeks) (108). Even preclinical trials report a significant increase in morbidity in mice when hyperthermia and bevacizumab are combined (109). At present, it is difficult to deprive a patient from a treatment based on Level I evidence suggesting an alternative therapeutic strategy that is not universally accepted because of the lack of irrefutable evidence.…”
Section: Topic 6: What Is the Best Timing As Far As Results Are Concementioning
confidence: 99%
“…The addition of bevacizumab to HIPEC has been shown in animal models to increase the intraperitoneal concentration of oxaliplatin but without an increase in efficacy. A retrospective study in humans found a higher postoperative complication rate, in particular, a greater chance of intra‐abdominal abscess, in patients who received HIPEC with bevacizumab compared with standard HIPEC . The combination of mitomycin C and hydrogen peroxide has been shown to increase the intraperitoneal concentration, whereas decreasing the serum concentration in a phase I trial, which could potentially lead to increased efficacy and decreased toxicity …”
Section: Surgical Therapymentioning
confidence: 99%
“…Hyperthermic intraperitoneal chemoperfusion (HIPEC) appears to be the most commonly used IPCP method providing better survival times, although it is currently not recommended as a standard-of-care option due to the controversy surrounding its use (21). In addition, there is no definitive proof supporting the advantage of HIPEC over normothermic IPCP, and accumulating preclinical data suggest that HIPEC has no advantage over IPCP (22)(23)(24). Hyperthermia has already been proven to be of no value in isolated limb chemoperfusion (25).…”
Section: Introductionmentioning
confidence: 98%